Identification of changes in the rainfall regime in Chihuahua’s state (México) - Mendoza Uribe, Indalecio (Cuadernos de Investigación Geográfica, 2022)
The impacts of Climate Change are not homogeneous globally or for a country or region as a whole. Consequently, it is essential to carry out studies to identify its effects in particular areas. Due to its geographical and topographic characteristics, Chihuahua’s state is vulnerable to the adverse effects of Climate Change. The scarce availability of water resources leads to problems of social pressure and economic impact. This paper analyzes the alteration of the rainfall regime in Chihuahua’s state and its association with Climate Change. For this, historical characterization is used; trend analysis using the Mann Kendall test; and calculation of 10 indices of climatic extremes proposed by the Group of Experts for Detection and Climate Change Indices for the precipitation variable. The results showed that the precipitation patterns in the south and southeast of Chihuahua’s state have been gradually modifying, with a downward trend in annual accumulated and reduction of wet days. Still, in counterpart, there is a slight intensification of extreme rainfall. This fact added to the growing demand for water resources in the entity, requests for public policies for sustainable management and responsible use by users. Otherwise, there is a risk of experiencing negative effects associated with the over-exploitation of water, not only for the resource users but also for the environment.